Silenced narratives of 'comfort women': Japanese women as gendered imperial subjects. - Tsukamoto, Sachiyo (Women's History Review, 2025)
More than thirty years have passed since Kim Hak-soon's courageous silence-breaking in 1991. Still, there is a paucity of research on the Japanese victims of the 'comfort women' system. The narratives of Japanese comfort women as gendered imperial subjects reveal that militarism and nationalism work hand in hand to mercilessly exploit women and to silence their voices of trauma as a strategy of statecraft. This article deconstructs various accounts of the hidden voices of some Japanese survivors with a focus on relationships between women and the state. To this end, this study will analyse the oral/written testimonies of comfort women who chose 'honourable death' with Japanese soldiers, five schoolgirls who volunteered to become comfort women, military typists who were forced to comfort stations and Okinawan women who were mobilised into comfort stations in preparation for the total war against the Allied Forces. Their silenced narratives offer profound insights into a specific form of Japanese nationalism with the emperor as the pinnacle.